The Impact of Training, Motivation, Job Satisfaction, and Employee Engagement on Employee Performance: A Literature Study and Comprehensive Model - Setiawan, Agus (Dinasti International Journal of Management Science, 2025)
The Influence of Training, Motivation, Job Satisfaction, and Employee Engagement on Employee Performance is a scientific article of literature study in the scope of the field of science. The purpose of this article is to build a hypothesis of the influence of variables that will be used in further research. The object of research is online libraries, Google Scholar, Mendeley, and other academic online media. The research method with library research is sourced from e-books and open-access e-journals. Qualitative descriptive analysis. The results of this article are: 1) Training has an effect on Employee Performance; 2) Motivation has an effect on Employee Performance; 3) Job Satisfaction has an effect on Employee Performance, and 4) Employee Engagement has an effect on Employee Performance.